Extremist Characteristics Based on Arrested Cases in Southeast Asia - Ismail, Ahmad Munawar; Mujani, Wan Kamal (Afkar: Jurnal Akidah dan Pemikiran Islam, 2023)
Various aspects such as character, thought, belief, speech, and action were observed to determine the traits of a typical human being. Identifying the characteristics of extremists can be challenging for society, and often only becomes apparent after an individual has been detained as an extremist offender. Religious extremist groups engage in subtle heresy by deviating from the authentic teachings of Islam and promoting these deviations to their adherents as a form of religious reform. This article will examine the transformation of heretics in Southeast Asia by describing extremist characteristics in select countries. This study employed qualitative methods, including content analysis, interviews, and focus group discussions, to investigate the involvement of experts and activists in the process of rehabilitating extremists. Data on the psychological rehabilitation of extremists was gathered and analyzed using authoritative sources such as the Qur’an, Hadith, and works by Muslim and Western scholars, with a focus on references related to Islam, extremism, and heresy. The study aimed to ascertain the attributes of the extremist who was apprehended and subjected to official scrutiny. The results will be applied to extremist traits data and indicators identified by national and international religious extremist researchers, including extremism analysts, university academics, and religious department officials. Consequently, this study can establish a standard indicator for identifying the characteristics of this group, aiding society in detecting and containing its associated movement.